Qualitative monitoring of corn silage stored in commercial bunker silos and used as feed for dairy cattle in the western region of Santa Catarina State, Brazil - Di Domenico Giombelli L.C.* (2019)
© 2019 Universidade Estadual de Londrina. All rights reserved.Corn ensiling is a feed preservation practice used for ruminant production. During the process of making and opening the silos, the quality of the silage may change due to the entrance of air, which can cause damage and decrease the voluntary intake of the animals. The objective of this work was to evaluate the chemical composition of corn silages during their use in commercial bunker silos, as well as to correlate this with qualitative and quantitative characteristics related to the silage making process. Technical data on silage making and samples were collected from 14 bunker silos, with five samples collected along each silo (at 10, 30, 50, 70 and 90% of their lengths); additionally, two sampling methodologies were compared (“W” vs. layer collections in silo panels: top, middle and bottom). The values for the pH and titratable acidity (TA) were significant (p < 0.05) in relation to the sampling method, where the pH of the top was higher (3.8±0.5) than that of the middle and the bottom layers (3.6±0.3 and 3.5±0.3); therefore, the TA was lower in the top of the silos. The dry matter, ashes, crude protein, neutral detergent fiber, acid detergent fiber, pH, TA, as well as the silo sampling method during the unloading of commercial bunker silos did not differ for any of the variables (p < 0.05). Also, the particle size did not differ during the unloading of the commercial bunker silos (p > 0.05). According to the collected technical data, 78.57% of the bunker silos were built directly on the ground, the harvesting equipment was mostly borrowed from municipalities or farmers' associations (for 35.7 and 28.5% of the farms, respectively), and in only 64.2% of the farms, the harvester was sharpened before silage cutting. Good practices were applied during the corn silage process and throughout the use of the silos, homogeneous quality was detected in the western region of Santa Catarina. Either “W” or layer collections can be used to sample corn silage.